Pengembangan Modul Proyek Penguatan Profil Pelajar Pancasila Berbasis Kisah Islami Untuk Siswa SMP - Ninik Setyorini; Abas Mansur Tamam; Rahmat Rosyidi (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The character of being devout, reverent to God Almighty, and having noble morals is one dimension within the Pancasila Student Profile, which is a goal of education. However, achieving this goal is not easy, as many challenges are faced. These challenges arise from external factors like globalization, social media, and distorted understandings, as well as internal factors within students. The Pancasila Student Profile Strengthening Project is expected to achieve this educational objective, but it is hindered by a lack of teaching materials, unengaging project modules, and irrelevance. Islamic stories sourced from the Qur'an and Sunnah can be an effective medium for instilling the character of being devout, reverent to God Almighty, and having noble morals. This study aims to develop a Pancasila Student Profile Strengthening Project module based on Islamic stories for junior high school students. The research method used is Research and Development (R&D) with the ADDIE model (analysis, design, development, implementation, and evaluation). Data collection techniques involved questionnaires distributed online via Google Forms. The stages in this research were analysis, design, development, implementation, and evaluation. The analysis stage involved analyzing the need for the project module and analyzing existing project modules. The analysis of project module needs was conducted by collecting data through the distribution of questionnaires to several teachers from various regions in Indonesia. Next was the design stage. This stage was referred to as the initial prototype, followed by the development stage. In the project module development stage, data collection involved validating the project module by three experts: a language expert, a material expert, and a media expert. After validation from the three experts, the next stage was implementation, which involved user validation testing. The final stage was evaluation, carried out by the three experts: a language expert, a material expert, and a media expert. The research results for the "Pancasila Student Profile Strengthening Project Module Based on Islamic Stories for Junior High School Students" contain stories taken from M. Quraish Shihab's book titled "Kisah-kisah dalam Al-Qur’an Makna dan Hikmah" (Stories in the Qur'an: Meaning and Wisdom) and Dr. Thal'at Muhammad 'Afifi Salim's book titled "Kisah-kisah Shahih dalam Sunnah" (Authentic Stories in the Sunnah). The validation test results from the language expert were 94.28% "Very Feasible," the material expert 93.33% "Very Feasible," and the media expert 95.00% "Very Feasible." The average value from the expert validation test was 94.20%, falling into the "Very Feasible" category.